2004
DOI: 10.1016/j.jmb.2004.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Human Alu Ya-lineage

Abstract: The Alu Ya-lineage is a group of related, short interspersed elements (SINEs) found in primates. This lineage includes subfamilies Ya1-Ya5, Ya5a2 and others. Some of these subfamilies are still actively mobilizing in the human genome. We have analyzed 2482 elements that reside in the human genome draft sequence and focused our analyses on the 2318 human autosomal Ya Alu elements. A total of 1470 autosomal loci were subjected to polymerase chain reaction (PCR)-based assays that allow analysis of individual Ya-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
2

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 53 publications
3
47
2
Order By: Relevance
“…We compared the distribution of allele frequencies for the Alu insertions with previously studied populations. 13,14,25,26 No significant differences between our and previously published results obtained for genetically and geographically distant populations (see Supplementary Table 1) were observed. These results suggest that the selected 32 Alu set can be successfully used for human genetic identification worldwide.…”
Section: Resultscontrasting
confidence: 66%
See 1 more Smart Citation
“…We compared the distribution of allele frequencies for the Alu insertions with previously studied populations. 13,14,25,26 No significant differences between our and previously published results obtained for genetically and geographically distant populations (see Supplementary Table 1) were observed. These results suggest that the selected 32 Alu set can be successfully used for human genetic identification worldwide.…”
Section: Resultscontrasting
confidence: 66%
“…In the past decade, progress in human genome sequencing and methods of comparative genomics resulted in the identification of a new type of MGMs based on retroelement (RE) insertion polymorphism. [11][12][13][14][15] Recent studies revealed the existence of several thousands of polymorphic RE insertions in the human genome. This type of MGMs has several peculiarities making them attractive for human genetic identification purposes: (i) RE insertions are stable, that is there is no specific mechanism for withdrawing or removing an element from its insertion point; (ii) the probability of independent RE insertion in the same genomic locus is negligibly small, and the presence of RE indicates identity by descent; and (iii) simple identification.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers familiar with Alu SINEs will be aware that distinct subfamilies of Alu exist in each primate lineage Hedges et al 2004;Otieno et al 2004;Garber et al 2005;Ray and Batzer 2005;Ray et al 2005b;Salem et al 2005b;Han et al 2007;Liu et al 2009;Locke et al 2011). Each of the methods described relies on sequence characteristics unique to particular subfamilies of elements.…”
Section: Extensions To Other Organismsmentioning
confidence: 99%
“…The remaining 46 CHGS polymorphic elements were likely from the public human BAC sequences that may have not been used for the assembly of PHGS. To determine how many of the 800 polymorphic Alu elements had been previously identified and published, we compiled a database containing 1051 non-redundant polymorphic Alu insertions (http://falcon.roswellpark.org:9090; Wang et al, in press) from the over 1500 polymorphisms reported in the literature (Batzer et al, 1994Bennett et al, 2004;Callinan et al, 2003;Carroll et al, 2001;Carter et al, 2004;Garber et al, 2005;Mamedov et al, 2005;Otieno et al, 2004;Ray et al, 2005;Roy-Engel et al, 2001;Watkins et al, 2003;Xing et al, 2003). A comparison of the genomic locations of our 800 polymorphic Alu insertions with the list revealed that only 266 of the 800 Alu elements correspond with previously reported Alu repeats, suggesting that the remaining 534 insertions represent newly identified polymorphisms.…”
Section: Identification Of Alu Insertion Polymorphismsmentioning
confidence: 99%
“…The first study using such a strategy identified 106 polymorphic Alu insertions out of 475 Ya5 and Yb8 insertions (Carroll et al, 2001). Subsequently, this method has been extensively used to analyze almost all Y subfamilies including Ya (Otieno et al, 2004), Yb (Carter et al, 2004;Roy-Engel et al, 2001), Yc (Roy-Engel et al, 2001;Garber et al, 2005), Yd (Xing et al, 2003), Yg and Yi (Salem et al, 2003), Ye (Salem et al, 2005b) and multiple Y subfamily members on the X chromosome (Callinan et al, 2003). These studies are responsible for the identification of the majority of the known polymorphic Alu insertions.…”
Section: Introductionmentioning
confidence: 99%